Exploring The Delightful Flavors Of Xie Wonton: A Culinary Journey Through Pangsit Perfection - Siska Hermansyah (Universitas Kristen Indonesia Toraja, 2024)
The internship activity of the Independent Campus program is the Independent Entrepreneurship (WMK) program which is held as a form of work training process in the entrepreneurial world to gain sufficient experience for students so that after graduating, they are ready to enter the real world of work. So the existence of the Certified Independent Entrepreneurship Internship (WMK) program is one way to improve the skills obtained apart from lectures in order to gain new knowledge and experience in the world of work which will be very beneficial when students graduate. The Independent Entrepreneurship (WMK) certified internship program can equip students with skills and also answer all entrepreneurship needs, especially in the field of computing and going directly into the community (Expo). This internship program runs for 4 months, starting from 8 August to 22 November. This internship program provides learning about entrepreneurship and a final project in the form of a report on entrepreneurial activities by going directly into the community for 2 days (Expo Day). In completing this final project, the same work method is used as an approach that will be carried out for each student. In this way, you have fulfilled the requirements to carry out the final project in this program.